PENGGUNAAN TEPUNG PISANG SIBERAS DENGAN TEPUNG UBI JALAR SUBSTITUSI TERIGU PADA PEMBUATAN MI KERING: KASUS DI PROVINSI SUMATERA UTARA - N.D.M. Romauli Hutabarat; Henri F. Purba (Balai Besar Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT The Use of “Siberas” Banana Flour Combinated with Sweet Potato Flour to Subtitute Wheat on the Processing of Dried Noddles: Case Study in North Sumatra Province. Most of bananas’ local varieties in North Sumatera are still consumed freshly from a table. This provides big opportunities for diversifying the processed product. Likewise, local varieties of sweet potato have not been processed to be various food yet. The aims of this research were: (i) to obtain a best ratio of composite flour of banana Siberas with orange sweet potato flour and wheat flour in dried noodles processing, and (ii) to determine the effect of drying method using sun only and sun combined with oven. This research was conducted at Post Harvest Laboratory of BPTP Medan from March until July 2014. Banana Siberas flour was added at the level of: 10; 20; 30; 40; and 50% combined with orange sweet potato flour and wheat flour at the level of 45; 40; 35; 30; and 25% for each. This research applied two drying methods, sun drying and its combination with oven drying. Based on the organoleptic test, the results showed that dried noodles from 10% of banana Siberas flour, 45% of orange sweet potato flour and 45% of wheat flour have the highest preference value. This composite flour producing dried noodles contains of water 6,62%, protein 3,41%, fiber 5,37% and carbohydrate 84,36%. Profit estimated from dried noodles using composite and wheat flour are Rp117.804,80 and Rp83.036,80 with the R/C of 1,31 and 1,19 respectively. Keywords: Siberas banana flour, orange sweet potatoes flour, dried noodles,drying methodABSTRAK Sebagian besar pisang varietas lokal di Sumatera Utara masih dikonsumsi dalan bentuk segar sebagai buah meja sehingga memberikan peluang besar diversifikasi hasil olahannya. Ubi jalar oranye varietas lokal masih belum banyak dimanfaatkan untuk menjadi produk olahan pangan. Tujuan penelitian: (i) untuk mendapatkan formulasi terbaik pembuatan mi kering menggunakan tepung komposit pisang Siberas dengan tepung ubi jalar oranye dan terigu; dan (ii) untuk mengetahui pengaruh metode pengeringan menggunakan sinar matahari dan kombinasi sinar matahari dengan oven. Pengkajian dilakukan di Medan, pada bulan Maret sampai bulan Juli 2014. Penambahan tepung pisang Siberas dilakukan pada taraf 10; 20; 30; 40; dan 50% yang dikombinasikan dengan tepung ubi jalar oranye dan tepung terigu 45; 40; 35; 30; dan 25%. Pengeringan mi kering dilakukan dengan dua metode yaitu sinar matahari dan kombinasi antara sinar matahari dan oven. Hasil uji organoleptik menunjukkan mi kering dengan tepung komposit yang terbuat dari 10% tepung pisang Siberas, 45% tepung ubi jalar oranye dan 45% tepung terigu memiliki nilai tingkat kesukaan yang paling tinggi. Mi kering dengan metode pengeringan kombinasi mengandung kadar air 6,62%, protein 3,41%, serat 5,37% dan karbohidrat 84,36%. Keuntungan yang diperoleh dari pembuatan mi kering dengan tepung komposit sebesar Rp117.804,80 lebih tinggi dibandingkan dengan tepung terigu (Rp83.036,80) dengan R/C berturut-turut 1,31 dan 1,19. Kata kunci: Tepung pisang Siberas, tepung ubi jalar oranye, mi kering, cara pengeringan